Genome-wide analyses of lung cancer after single high-dose radiation at five time points (2, 6, 12, 24, and 48 h) - Du, Yajing; Zheng, Yunna; Yu, Kaiwen; Zhan, Cheng; Qiao, Tiankui (Frontiers in Genetics, 2023)
Background More and more clinicians are experimenting with high-dose radiation. This study focuses on the genomic effects of high-dose-single-shot radiotherapy and aims to provide a dynamic map in non-small cell lung cancer (NSCLC). Methods We used whole-transcriptome sequencing to understand the evolution at molecular levels in A549 and H1299 exposed to 10Gy X-rays at different times (2, 6, 12, 24, and 48h) in comparison with the no radiation group. Ingenuity pathway analysis,ceRNA analysis, enrichment analysis, and cell cycle experiments are performed for molecular analyses and function analysis. Results Whole transcription sequence of NSCLC was in a significant dynamic change after radiotherapy within 48 hours. MiR-219-1-3p and miR-221-3p, miR-503-5p, hsa-miR-455-5p, hsa-miR-29-3p and hsa-miR-339-5p were located in the core of the ceRNA related to the time change. GO and KEGG analysis of the top 30 mRNA included DNA repair, autophagy, apoptosis, and ferroptosis pathways. Regulation of cell cycle-related transcription factor E2F1 might have a key role in the early stage of radiotherapy(2,6h) and autophagy in the later stage(24,48h). Functions involving different genes/proteins over multiple periods implied a dose of 10 Gy was related to the kidney and liver pathway. Radiation-induced cell cycle arrest at the G2/M phase, obviously at 24 hours. We also observed increased expression of CCNB1 at 24h in PCR and WB experiments.